Effective Chiral Interactions between Nonchiral Rigid Macromolecules in a Chiral Solvent and the Induced Cholesteric Liquid Crystal Phase - Mikhail A. Osipov; Alexey S. Merekalov (Crystals, 2022)
It has been shown that a nonchiral anisotropic macromolecule embedded in a chiral dielectric solvent possesses an effective optical activity proportional to the optical activity of the solvent. As a result, there exists an effective chiral interaction between the macromolecules, which creates a torque acting on the primary axes of the two interacting molecules. A general expression for the effective chiral interaction potential has been derived in terms of the effective polarizability and the effective gyration tensor of the macromolecule in the chiral solvent. Explicit expressions for the components of the effective polarizability and the gyration have been obtained using the model of a hard rod filled with anisotropic dielectric and embedded into the isotropic chiral dielectric medium. The theory predicts the formation of the cholesteric helical structure in the nematic polymer liquid crystal phase induced by a chiral solvent.